Efeitos dos processos bióticos e abióticos na diversificação dos neoselacchii - Fernandes, Elisa Cravo (2019)
Events of extinctions and species replacement are ubiquitous in the Earth’s evolutionary history, being driven by biotic and abiotic factors. Knowledge about evolutionary patterns in the marine environment is still scarce, since most studies are conducted in the terrestrial environment. The Neoselachii, clade which originated in the Carboniferous period and experimented its greater diversification during the Jurassic-Cretaceous, faced the last three great extinctions. In this work we analyse the species speciation, extinction and diversification rates for sharks and rays in order to evaluate if and how the last three mass extinctions influenced the Neoselachii diversification at clade and order level. We also evaluated whether environmental changes and ecological interactions affected the extinction rates of Neoselachii orders. Our results showed that mass extinctions did not influence the diversification rates of the group. However, there was an increase in the extinction rate at the end of the Miocene, coinciding with events of background extinctions that occurred at this time. The data obtained through the diversification analysis were associated with environmental changes of the Miocene period and the diversification of putative competitive groups - Delphinidae (Mammals: Odontoceti). We found that decrease in temperature and sea level oscillations caused an increase in the extinction rates of the analyzed orders. Our results also indicate that intraclass and intercalated competition negatively influenced extinction rates. Understanding how biotic and abiotic factors affect organisms provides important information about current biodiversity and the consequences of future events that may occur. Therefore, the study of extinct and current organisms assists in the prediction of impacts of future environmental changes. Thus, it is expected that the results presented here will provide a basis for a possible prediction of how this group will react in extinctions future events.